Pola Perjalanan Siswa Sekolah Dasar Di Kecamatan Semarang Tengah - Endra Nugraha; Diah Intan Kusumo Dewi (Jurusan Perencanaan Wilayah dan Kota, 2018)
The destination of travel to work place and educational facilities are called as main trip which is a daily routine, on the other hand, another trip is a choice, not a routine (Tamin, 2000). One of the travel type which is interested to be studied is a travel of elementary students to their schools. This travel has to be considered because there is a physical constraint of students which cause the different trip with adult. The objective of this research is to identify the travel pattern from various trips of individual who are doing the trip to elementary school. By knowing the various characteristics of student’s trip to school, there will be a way to know the problems caused by the trip process. This research is done in Semarang Tengah District and it is a central urban zone which can cause effects to the students of elementary school in terms of travel pattern. Data is collected by doing survey to the households which have children aged at elementary school. Method used in this research is quantitative method. Quantitative-descriptive analysis method with analysis to the frequency distribution and spatial using GIS. The results show that there is a trip pattern of elementary students in Semarang Tengah district, particularly regarding the mode preference and route choice which is determined by age, vehicle owning, time, and distance. On the other side, same time to go to school and going to work by parents only affect the trip to school with private car. The most used transportation mode is with motorcycle and by passing the fastest route